1986
DOI: 10.1161/01.str.17.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit as a risk factor of cerebral infarction: long-term prospective population survey in a Japanese rural community.

Abstract: SUMMARY l b elucidate the relation of hematocrit (Hct) to the incidence of cerebral infarction, a prospective follow-up study of 16 years (1965-81) was performed in a general population sample of 1220 Hisayama residents aged 44 and over, of both sexes. Most of the subjects who died during the follow-up period were autopskd, the rate being 89.0%.Hct decreased with advancing age in men, but not in women. The average value for Hct was significantly lower in women than in men. According to the mean value ± 1 SD of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
3
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 20 publications
3
31
3
1
Order By: Relevance
“…[393][394][395] In addition, elevated fibrinogen levels, which add to plasma viscosity, have been documented. On the basis of these findings, hemodilution, with or without venesection, has been studied.…”
Section: A Hemodilution In Acute Ischemic Strokementioning
confidence: 99%
“…[393][394][395] In addition, elevated fibrinogen levels, which add to plasma viscosity, have been documented. On the basis of these findings, hemodilution, with or without venesection, has been studied.…”
Section: A Hemodilution In Acute Ischemic Strokementioning
confidence: 99%
“…This is in strong contrast to findings from the general population, in which high, not low, hemoglobin was associated with an increased risk (33)(34)(35)(36). However, these studies may have had insufficient power to detect an association between very low hemoglobin levels and stroke given the low prevalence of severe anemia in the non-ESRD population.…”
Section: Discussionmentioning
confidence: 58%
“…Another recent report 7 shows that mean hematocrit decreases from cases with transient ischemic attacks (46%) to cases with reversible ischemic neurologic deficit (45%) to cases with completed stroke (44%). As regards this negative role 21 has shown that cerebral infarction incidence is increased in women (but not in men) with low hematocrit. The authors of this study comment that one of the reasons for this relation could be that low hematocrit is related to reduced tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%